PERAN SISTEM INFORMASI MANAJEMEN DALAM OPTIMALISASI PENGELOLAAN DATA PASIEN DI FASILITAS PELAYANAN KESEHATAN - Saipul Bahari; Muhammad Irwan Padli Nasution (INTERNATIONAL, Journal of Sharia Business Management, 2025)
Management Information Systems (MIS) play an increasingly significant role in enhancing the quality of healthcare services. This research explores how MIS improves the management of patient data, focusing on faster information access, improved data accuracy, and smoother coordination across medical units. Through literature review and observation of MIS usage in several healthcare facilities, the study reveals that MIS reduces data entry mistakes, accelerates service delivery, and strengthens the protection of patient data. In addition, MIS facilitates clinical decision-making by offering well-organized and easily retrievable information for healthcare staff. In conclusion, the study highlights that effective MIS utilization greatly contributes to achieving patient data management that is more efficient, clear, and sustainable in healthcare environments.